The Influence Of Incentives And Intrinsic Motivation On The Work Spirit Of Employees Of In Regional Public Company West Java: PENGARUH INSENTIF DAN MOTIVASI INTRINSIC TERHADAP SEMANGAT KERJA KARYAWAN PT PDAM TIRTA JATI KOTA CIREBON - Rr Putri Ika Riani Pramesti; Nida Arifiani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study investigates the impact of incentives and intrinsic motivation on employee morale at PDAM Tirta Jati Cirebon Regency. The research used quantitative techniques, including observational data gathering and questionnaires, with 149 participants. The study used SPSS Version 25.0 for data analysis. The results indicated that incentives (β = 0.360, t = 5.623, p = 0.000) did not significantly influence employee morale on an individual level, but they did positively contribute to it when combined with intrinsic motivation. Intrinsic motivation (β = 0.490, t = 3.586, p = 0.000) showed a significant positive impact on employee morale. The simultaneous significance test revealed that employee morale is significantly impacted by the combination of incentives, intrinsic motivation, and job excitement (F = 32.926, p < 0.001), with these factors collectively explaining 30.3% of the variance in employee morale (Adjusted R² = 0.303). This highlights the importance of intrinsic motivation and work enthusiasm in improving employees in the PDAM Tirta Jati Cirebon District environment. The research's limitations include its focus on PDAM Tirta Jati Cirebon district employees, which may limit its generalizability. Future research could explore other organizational contexts to increase the generalizability of the results